THE ADHERENCE OF INSULIN-BASED THERAPY ON THE PATIENTS OF TYPE 2 DIABETES MELITUS IN ENDROCRINOLOGY POLYCLINIC OF DR SARDJITO HOSPITAL YOGYAKARTA - Risya Mulyani; Tri Murti Andayani; I Dewa Putu Pramantara S (Faculty of Pharmacy, Universitas Gadjah Mada)
Diabetes mellitus may cause significant problems on quality of life through the increasing risks of the occurrence of various complications. Lack of knowledge regarding disease and medication, disobedience of the patient to medication and dissatisfaction with the therapy also contribute to the poor blood glucose control. The aim of this study was to determine medication adherence and its association with blood glycemic control (HbA1c value). This research belongs to cross-sectional research in which sampling was conducted prospectively by performing purposive sampling on type 2 DM patients in Endocrinology Polyclinic of DR Sardjito Hospital from November 2011 until January 2012. Assessment of therapy adherence was conducted using MMAS-8 and data of blood glucose control were collected through examination of HbA1c value. Questionnaires completed by study subjects as much as 109 respondents were analyzed using bivariate analysis the chi-square test. The result showed that there was only 41,3% patients who adhered to the therapy, while 58,7% was considered to disobey the therapy. In addition, respondents with good glycemic control (<6,5%) were only 41,3%, while the remaining 58,7% was considered poor. There was significant correlation of the therapy type on the adherence level (r =-0,449; p<0,05). Moreover, there was significant correlation of disease duration on the adherence level (r =-0,584; p<0,05). There was significant correlation of the adherence level on the HbA1c value (r =0,931; p<0,05). Keywords: Diabetes mellitus, therapy adherence and HbA1c value.